If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying u(x) = 3x + -4 Multiply u * x ux = 3x + -4 Reorder the terms: ux = -4 + 3x Solving ux = -4 + 3x Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Divide each side by 'x'. u = -4x-1 + 3 Simplifying u = -4x-1 + 3 Reorder the terms: u = 3 + -4x-1
| 300-10y+25y=5.10 | | -16x^2+300=100 | | -16x^2+300=0 | | x=10/3 | | 5/12=x/8 | | -16x^2+52x+16=0 | | 7+(1/2)x=4 | | 2z+16+3z=16 | | 3(2x+5)-9= | | -18=w/2-8 | | X-2(x-20)=3x | | X-2(x-20)=3 | | 6x+4-3= | | 3v+4=-14 | | 14y/5-13=10 | | 0.40x(0.50x)-0.50x=500 | | x^2+9x/2-5/2 | | (1/3)x+5=4 | | 1-2/3(1/2+2x)=-x/3 | | 3w-3-w^2=0 | | 0.50x+0.40*0.50=500 | | 32-3-w^2=0 | | 0.40*0.50x-0.50x=500 | | x-2x+13squared=-7 | | -2v^2+8v-8=0 | | x^2+36-8x=0 | | 3(3x-9)/2=5(9x-3)/4 | | 9w(3x+2)= | | (X+8)/3=x | | 80x=20 | | 3(x^2+6x+9)=0 | | x=51 |